Influence of types of binder and plant aggregates on hygrothermal and mechanical properties of vegetal concretes. (20th October 2019) - Lagouin, Méryl; Magniont, Camille; Sénéchal, Pascale; Moonen, Peter; Aubert, Jean-Emmanuel; Laborel-préneron, Aurélie
Highlights: Pore structure of bio-based materials is investigated combining WIP, MIP and X-ray CT. X-ray CT is a promising tool for the exploration of inner porosity of plant particles. Hygrothermal properties and compressive strength are measured on bio-based concretes. Types of binder and aggregate impact the use performances of vegetal concretes. Abstract: Bio-aggregate based building materials offer promising perspectives thanks to their low environmental impact and interesting hygrothermal behaviour. In this paper, different formulations of bio-aggregate concrete are proposed and analysed. We focus on two types of locally available bio-aggregates, namely maize and sunflower bark chips, and two types of binder matrices, based on respectively metakaolin and lime. The study specifically focuses on the pore structure of the composite material, as this quantity has a decisive impact on the insulating properties (thermal conductivity), the hygric behaviour (sorption isotherms, water vapour permeability and moisture buffer value) as well as on the mechanical performance (compressive strength). The results underline the impact of the constituents' porosity on the complex porous structure of the bio-concrete and the influence of porosity on its performance. The findings demonstrate that metakaolin and sunflower are high-potential raw materials for the design of a bio-aggregate based concrete.